2018
DOI: 10.1007/s11465-018-0504-z
|View full text |Cite
|
Sign up to set email alerts
|

A review on ductile mode cutting of brittle materials

Abstract: Brittle materials have been widely employed for industrial applications due to their excellent mechanical, optical, physical and chemical properties. But obtaining smooth and damage-free surface on brittle materials by traditional machining methods like grinding, lapping and polishing is very costly and extremely time consuming. Ductile mode cutting is a very promising way to achieve high quality and crack-free surfaces of brittle materials. Thus the study of ductile mode cutting of brittle materials has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(24 citation statements)
references
References 100 publications
1
22
0
Order By: Relevance
“…Several researchers, since the late 1950s, have investigated the ductile SPE behaviour of materials. Finnie [53] was the first to model the mechanism, on the basis of the cutting of the surface by the impacting particles. Biswas et al [54] experimentally investigated the response of mild steel and aluminium surfaces, to SPE using angular silicon carbide (SiC) particles with radius 60 µm.…”
Section: Ductile Solid Particles Erosion (Spe) Mechanismmentioning
confidence: 99%
“…Several researchers, since the late 1950s, have investigated the ductile SPE behaviour of materials. Finnie [53] was the first to model the mechanism, on the basis of the cutting of the surface by the impacting particles. Biswas et al [54] experimentally investigated the response of mild steel and aluminium surfaces, to SPE using angular silicon carbide (SiC) particles with radius 60 µm.…”
Section: Ductile Solid Particles Erosion (Spe) Mechanismmentioning
confidence: 99%
“…Researchers have concluded that there is plastic deformation in the micro-nano machining process of brittle materials, such that machined surface damage will be avoided and high surface quality can be achieved [26][27][28][29]. The most widely adopted model to explain brittle material deformation is that developed by Lawn et al [30], shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…For ceramics, SiC was studied [12][13][14] intensely; but also, elemental Si was investigated repeatedly [3,9,[15][16][17] as a prototypical example of a brittle material, even if it is not a ceramic in the strict sense of the word. Several studies found that, in the nanoscale, these materials behave in a ductile way; this phenomenon was termed the "brittleductile transition" since seemingly brittle materials change their behavior and show ductile features [18][19][20].…”
Section: Introductionmentioning
confidence: 99%